Design and characterisation of reclaimed asphalt mixtures with biobinders - Jiménez del Barco Carrión, Ana (2017)
Most pavements around the world are built with asphalt mixtures. Traditional asphalt mixtures are composed of aggregates and bitumen. Current concern about environmental issues and scarcity of these raw materials has motivated the search for different recycled and renewable resources to be used in pavement engineering. Regarding recycling, the use of Reclaimed Asphalt (RA) materials is nowadays a common and valued practice. However, there still exist some concern about its performance when used in high amounts (>30%) due to its aged state. In terms of renewable resources, the relatively new concept of biobinders (binders manufactured from biomass), as suitable asphalt binder alternatives, is gaining force in pavement engineering. To date, biobinders have shown great potential not only to reduce bitumen demand, but also exhibiting good performance in terms of resisting the main distresses affecting pavements. However, biobinders need in-depth and detailed characterisation in terms of engineering properties before they can be used in practice. The combination of RA and biobinders can be considered as an innovative technique to reduce the consumption of aggregates and bitumen. Within this framework, the main aim of the research described in this thesis was to study the performance of RA mixtures with biobinders at binder and mixture scale in order to gain further understanding of their suitability to be used in actual pavements. For this purpose, biobinders manufactured from pine resin, linseed oil and by-products of the paper industry have been investigated as binders for the total replacement of the virgin bitumen needed in high RA content asphalt mixtures. The research initially focused on the design of the blend of RA binder and biobinders through the study of their conventional and rheological properties which were subsequently used as an input in the design of the asphalt mixtures. Once the design parameters were fixed, the blends of RA binder and biobinders were characterised in terms of their rheological, ageing and adhesion properties, and their performance tested in terms of study rutting, fatigue and thermal cracking resistance. Then, 50% RA mixtures and 70% RA mixtures were characterised for the same properties and the relationships between binder blends and asphalt mixtures were studied. The results showed that the biobinders studied are viscoelastic materials able to efficiently restore some of the properties of the RA binder in an equivalent or better way than conventional bitumens, increasing its viscous component and decreasing its stiffness. The mechanical performance of biobinders and bio-asphalt mixtures regarding rutting, fatigue, thermal cracking and moisture damage was found to be comparable to conventional mixtures. Good relationships were found between the binder blends and asphalt mixtures performance under the assumption of full blending, even though the exact degree of blending remained unknown. In this regard, the blend design performed as the first step was found to satisfactorily work as the input for the design of high RA content asphalt mixtures. Biobinders and bio-asphalt mixtures showed the same ageing tendency as conventional materials although ageing occurred at a faster rate, which can be considered the main drawback of their performance. In the light of the results obtained in this thesis for the materials studied, high RA content asphalt mixtures with biobinders can be considered promising materials to be used in pavement engineering. Full-scale experiments could be the final step for their development.